Perkosaan dalam Rumah Tangga (Marital Rape) dalam Perspektif Maqāṣid al-Sharī’ah - Martyana, Karina; Munir, Muhammad Syahrul (Program Studi Hukum Ekonomi Syariah, 2022)
Sexual violence requires special attention and handling in law enforcement in Indonesia because it has permeated every element of human life, including within the scope of the household or marriage. Marital rape has a similar impact to the impact of marital rape outside of marriage, so it is not fair to distinguish rape that occurs outside or inside marriage because it is closely related to sexual justice and gender equality. The formulation of the problem in this study is how the general picture of domestic rape, how domestic rape is in the dynamics of law in Indonesia, and how rape in the household in the perspective of maqāṣid al-sharī'ah. This research includes library research with data collection methods contained in books or journals that have a relationship with discussion. The results of this study show that marital rape is an act of violence or coercion committed by the husband against the wife to carry out sexual activity without considering the condition of the wife. Marital rape has a severe impact on the victim, such as damage to the reproductive apparatus, damage to the menstrual cycle, and the possibility of beatings from the husband which then have a trauma impact. In The Criminal Code, marital rape complaint cannot be declared an act of rape of the husband against the wife, but is said to be a criminal act of mistreatment. In terms of maqāṣid al-sharī'ah the act of marital rape does not reflect the fulfillment of the purpose of sharia in marriage, especially from maslahah al-daruriyyah, namely hifdz an-nafs and hifdz an-nasl.